Go West, Oxen, Horses, and Mules: Review of Diana L. Ahmad, Success Depends on the Animals: Emigrants, Livestock, and Wild Animals on the Overland Trails, 1840–1869 - Erby, Kelly (Humanimalia, 2019)
Diana L. Ahmad. Success Depends on the Animals: Emigrants, Livestock, and Wild Animals on the Overland Trails, 1840–1869. x + 132 pp., notes, bibliography, index. Las Vegas: University of Nevada Press, 2016. 31.95 (hb).